Kalam Allah: Tumpuan Terhadap Penghujahan al-Qadi 'Abd al-Jabbar - Mohd Radhi Ibrahim (2024)
The aim of this article is to examine the polemic between Islamic Theologians regarding the speech of God, with special attention to al-Qadi 'Abd al-Jabbar's arguments.